Chromosome-level genome assemblies of sunflower oilseed and confectionery cultivars - Liuxi Yi; Haizhu Bao; Yang Wu; Yingnan Mu; Chao Du; Jingwen Peng; Xuechun Yan; Yongsheng Chen; Haifeng Yu (Scientific Data)
Abstract The sunflower (Helianthus annuus L.), belonging to the Asteraceae family, is the world’s fourth most important oil crop. Sunflower cultivars are categorized into oilseed and confectionery types. Here, we present chromosome-level genome assemblies of two Chinese sunflower cultivars-oilseed and confectionery-using PacBio HiFi and Hi-C sequencing. The oilseed cultivar, OXS, has a genome assembly spanning 3.03 Gb with 99.58% of sequences anchored to 17 chromosomes and a contig N50 length of 154.78 Mb. The first published confectionery cultivar genome, YDS, mirrors this closely with a 3.02 Gb assembly, contig N50 length of 153.87 Mb and 99.40% of sequences mapped similarly. Gene completeness reached 98.2% for OXS and 98.4% for YDS, with LTR Assembly Index scores of 24.73 and 25.85, respectively. Comparative genomics identified rapidly evolving gene families linked to synthesis, growth, and stress defense. Additionally, we found high collinearity between the YDS and OXS genomes, despite three significant inversions, and detected 15,056 large deletions and insertions. These findings lay a robust foundation for advanced genomic research and breeding innovations in sunflowers.